The development of pedagogical infrastructures in three cycles of maker-centered learning projects - Riikonen, Sini Maarit; Kangas, Kaiju; Kokko, Sirpa; Korhonen, Tiina; Hakkarainen, Kai; Seitamaa-Hakkarainen, Pirita (Design and Technology Education: An International Journal, 2020)
The purpose of the present investigation was to analyze the pedagogical infrastructures in three cycles of seventh graders’ co-invention projects that involved using traditional and digital fabrication technologies for inventing and creating complex artefacts. The aim of the projects was to create high-end multi-material makerspaces by expanding Finnish craft classrooms with instruments of digital fabrication, such as micro-processors, wearable computing (e-textiles), and 3D design and making, for enabling creation of student-designed multi-faceted inventions. Through a qualitative meta-analysis of the three successive learning-by-making projects, we explored the kinds of pedagogical infrastructures required for fostering knowledge-creating practices of learning. Pedagogic infrastructures refer to the designed arrangements and underlying conditions of implementing an extensive study project in classroom practices needed for reaching the learning objectives. We analyzed the epistemological, scaffolding, social, and material-technological dimensions of the enacted pedagogic infrastructures. In accordance with design-based educational investigations, we collected a variety of data (classroom video recordings, teacher and tutor interviews, invention challenges, learning assignments, and working schedules) across three year-long developmental cycles. We discuss the limitations and opportunities of maker-centered learning settings as well as considerations for future development of makerspace as pedagogical innovations for integrating socio-digital and material-technical practices and spaces for learning